Regional cooperative security - Jarrín, Osvaldo (2016)
The author reflects upon the conditions in which poor countries are vulnerable to several sources of insecurity. In this context, the article explores the case of Colombia, a country threatened by drug trafficking and guerrilla warfare, and links the Colombian conflict to regional stability and peace. The author concludes suggesting three possible scenarios for the conflict in Colombia, and its consequences for the region. Finally, he argues for a collective security approach as a feasible response to these challenges.